Da adesão à assinatura, a política do nome próprio no Plano de Ações Articuladas – PAR – em Mato Grosso - Souza, Márcia Helena de Moraes (2015)
This study deals with the investigation of unfolding in Mato Grosso, an education policy implementation of the Federal Government, starting in 2007. The Education Development Plan (PDE) and the Target Plan Commitment All for Education (Decree N° 6094 of April 24, 2007) brought the Articulated Actions Plan (PAR), as a strategic planning tool, used by the Ministry of Education for mapping the education’s reality in the states and counties, and invested in the execution of a collaborative system, constitutionally proposed for federal entities searching for improvement of basic education’s qualitative results. In order to discuss the management of public education policy, the Municipal Secretaries as interlocutors were elected to address two philosophical concepts indicated by the FrenchAlgerian philosopher Jacques Derrida; proper noun policy, and signature. The longitudinal monitoring of these actions implemented between 2007 and 2014 opens the way for discussions on the National Education System’s construction, determined by the National Education Plan 2014-2024. The view is that the different methods of signature, in the accession process of managers to the national policy impacted the conduction of joint, required in the collaboration scheme for federal entities, independent and autonomous in relation to education. The limits of geographic space, the boundaries of political space and the public-private relationship in public administration, are the issues discussed from the research results.